Pioglitazone and risk of mortality in patients with type 2 diabetes: results from a European multidatabase cohort study. Issue 1 (29th May 2017) - Strongman, Helen; Korhonen, Pasi; Williams, Rachael; Bahmanyar, Shahram; Hoti, Fabian; Christopher, Solomon; Majak, Maila; Kool-Houweling, Leanne; Linder, Marie; Dolin, Paul; Heintjes, Edith M
Abstract : Objectives: Estimate and compare the risk of mortality in patients whose antidiabetic therapy is modified to include pioglitazone compared with an alternative antidiabetic medication at the same stage of disease progression. Design: Retrospective cohort study. Setting: Pooled analysis of clinical data collected from primary and/or secondary care settings in four European countries: Finland, The Netherlands, Sweden and the UK . Participants: 56 337 patients with type 2 diabetes mellitus first prescribed pioglitazone between 2000 and 2011, and 56 337 patients never prescribed pioglitazone matched by treatment stage, history of diabetes, diabetes complications and cardiovascular disease, and year of cohort entry using exact and propensity score matching. Patients were followed-up for a mean of 2.90 (SD 2.21) and 2.83 (SD 2.37) years in the pioglitazone-exposed and non-pioglitazone-exposed groups, respectively. Outcomes: All-cause mortality ascertained from clinical or registry data. Mortality was a planned secondary outcome in a study primarily studying the association of pioglitazone use with bladder cancer risk. Results: The crude overall mortality rate per 10 000 patient years was 206 (95% CI 199 to 213) in the pioglitazone-exposed group and 448 (95% CI 438 to 458) in the non-pioglitazone-exposed group. The crude HR comparing pioglitazone to alternative antidiabetic exposure was 0.46 (95% CI 0.45 to 0.48). This reduced in magnitude to 0.67 (95% CI 0.64 to 0.70) following further adjustment for matching variables, propensity scores, age, gender and time-dependent variables representing use of alternative antidiabetic drugs. Conclusions: In this large observational cohort study of patients with type 2 diabetes, pioglitazone exposure was associated with a statistically significant decrease in the risk of all-cause mortality across four European countries. Results should be interpreted with caution due to the potential for residual confounding. Protocol registration: European Network of Centres for Pharmacoepidemiology and Pharmacovigilance.